Book Reviews. Issue 2 (1st June 2017) - Purin, Peter; Adamson, Charles D.; Rush, Adam
The Shuberts and their passing shows: The untold tale of Ziegfeld's rivals, Jonas Westover (2016)New York: Oxford University Press, 281 pp., ISBN: 978-0-19-021923-9, h/bk, £25.99Her turn on stage: The role of women in musical theatre, Grace Barnes (2015)Jefferson, NC: McFarland & Company, 210 pp., ISBN: 9780786498611, p/bk, 45.00 (United States)The Oxford handbook of the British musical, Robert Gordon and Olaf Jubin (Eds) (2017)New York: Oxford University Press, 776 pp., ISBN: 9780199988747, h/bk, £97